Autonomy and Solidarity in School Culture: A Relationality Perspective on Teacher Autonomy - Ince, Mehmet Akif; Tikkanen, Jenni (John Wiley & Sons, 2026)
This study examines teacher autonomy through a relationality perspective that challenges traditional conceptualisations of autonomy as solely individual control. Through an in-depth reflexive thematic analysis of interviews with nine Finnish teachers, the research reveals five interconnected themes showing how autonomy emerges within organisational structures and collaborative practices: sense of autonomy and organisational socialisation; interdependence and shared responsibility in school culture; curriculum-infused sense of responsibility; planning mindset synchronised by coursebooks; and testing as more than assessing students. These themes demonstrate that professional decision-making develops through socialisation, supported by curriculum frameworks and coursebook-guided practices. Additionally, testing practices exemplify how autonomy operates through relational dynamics, serving both assessment and stakeholder engagement functions. The data illustrate how teacher autonomy operates through these relational dimensions, offering valuable insights for reconceptualising it beyond individualistic frameworks that position autonomy in opposition to social and institutional structures and attempt to measure it as freedom from external constraints.